2014
DOI: 10.1101/008854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myoinhibitory peptide regulates feeding in the marine annelidPlatynereis

Abstract: Background: During larval settlement and metamorphosis, marine invertebrates undergo changes in habitat, morphology, behavior and physiology. This change between life-cycle stages is often associated with a change in diet or a transition between a non-feeding and a feeding form. How larvae regulate changes in feeding during this life-cycle transition is not well understood. Neuropeptides are known to regulate several aspects of feeding, such as food search, ingestion and digestion. The marine annelid Platynere… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 60 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…To further characterize nervous system anatomy using cell‐specific markers, we decided to also use neuropeptide antibodies. Several antibodies recognizing annelid neuropeptides have been developed for the nereid annelid Platynereis dumerilii (Conzelmann et al, ; Conzelmann & Jékely, ; Shahidi et al, 2015; Williams et al, ; Williams et al, ). To check the conservation of the Platynereis peptides in the three species we searched in the available transcriptomes of D. gyrociliatus (SRX2030658, Kerbl et al, ), D. taeniatus (SRX1025580, Andrade et al ) and T. axi (SRR2014693, Struck et al ), where we identified homologs for several Platynereis proneuropeptides in at least one of the species (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To further characterize nervous system anatomy using cell‐specific markers, we decided to also use neuropeptide antibodies. Several antibodies recognizing annelid neuropeptides have been developed for the nereid annelid Platynereis dumerilii (Conzelmann et al, ; Conzelmann & Jékely, ; Shahidi et al, 2015; Williams et al, ; Williams et al, ). To check the conservation of the Platynereis peptides in the three species we searched in the available transcriptomes of D. gyrociliatus (SRX2030658, Kerbl et al, ), D. taeniatus (SRX1025580, Andrade et al ) and T. axi (SRR2014693, Struck et al ), where we identified homologs for several Platynereis proneuropeptides in at least one of the species (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The specificity of these antibodies against AT, FVamide (FV), and MIP was tested by morpholino gene knockdown in larvae of P. dumerilii (Shahidi, Williams, Conzelmann, Asadulina, Verasztó, Jasek, Bezares‐Calderón, Jékely, & Calabrese, 2015; Williams et al, ), and the specificity of antibodies against calcitonin (CT), DLamide (DL), excitatory peptide (EP), FLamide (FL), FV, FVRIamide (FVRI), MLD/pedal peptide (MLD), RGW, RNamide/sCAP (sCAP), SIFamide (SIF), and VT was tested by whole mount in situ hybridization in larvae (Tables , , Jékely, ; Conzelmann et al, ; Asadulina, Panzera, Verasztó, Liebig, & Jékely, ; Conzelmann & Jékely, ; Shahidi et al, 2015; Williams et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive complement of neuropeptides has been described for this species, consisting of 100 proneuropeptide genes (12). Several of these neuropeptides have been mapped to the nervous system and have been studied functionally (13)(14)(15)(16)(17). Furthermore, .20 different neuropeptide and monoamine GPCRs have been experimentally identified in Platynereis, including the founding members of several major bilaterian neuropeptide-receptor families (achatin, FMRFamide, RGWamide, FLamide, and elevenin receptors) and the first invertebrate adrenergic receptors (17)(18)(19).…”
mentioning
confidence: 99%